Menanamkan Cinta Budaya Sejak Dini melalui Kunjungan ke Museum Pangeran Cakrabuana Kabupaten Cirebon - Yunus Husna Wijaya; Iman Hermanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of educational visits to the Pangeran Cakrabuana Museum in Cirebon Regency in fostering cultural awareness and appreciation among elementary school students. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation during museum visit activities. The findings indicate that the museum functions as an effective experiential learning medium for introducing local history and cultural heritage. Through direct interaction with historical collections, including heirlooms, ancient manuscripts, and cultural artifacts of Cirebon, students gained meaningful learning experiences that were more engaging and easier to understand than conventional classroom instruction. The educational visits significantly enhanced students’ knowledge of local history, strengthened their pride in regional cultural identity, and increased their interest in preserving cultural heritage. In addition, the museum serves not only as an educational institution but also as an important center for safeguarding and transmitting cultural values to younger generations. The integration of museum-based learning with classroom instruction provides students with authentic learning experiences that encourage active participation and deeper understanding of cultural diversity. Therefore, educational visits to the Pangeran Cakrabuana Museum represent an effective experiential learning strategy for strengthening cultural awareness, preserving local heritage, and developing students’ appreciation of regional identity from an early age.